Eco-Friendly Materials for Temporary Use in Architecture and Decorations - Walanrak Poomchalit; Ponlapath Tipboonsri; Boonsong Chongkolnee; Supaaek Pramoonmak; Watthanaphon Cheewawuttipong; Anin Memon (HighTech and Innovation Journal)
This paper introduces the development of ecologically friendly composite materials for decoration and architectural purposes. The composites designed comprised degradable polylactic acid (PLA) and sugarcane bagasse fiber (SC) derived from the bioplastics and sugar industries. The SC reinforcement was examined for impurity treatment and composite formation using hot compression molding at 200 ± 10°C. Two processing methods were studied: (1) random dispersion of SC at 0, 2, 4, 6, 8, and 10 wt%, and (2) single and double-layer SC composite sheets made with 6 wt% SC. The physical and mechanical properties of the PLA-SC composites were evaluated through the morphologies and flexural properties (ASTM C293), thermal conductivity (ASTM C518), and biodegradation assessment (ISO 16929:2021). Results revealed that impurities in SC were effectively removed using an alkaline sodium bicarbonate solution followed by boiling in a 5% vinegar solution. Increasing SC contents reduced the weight, density, and thermal conductivity (k-value) of the PLA-SC composites compared to those representing single and double layers of SC. Additionally, this approach enhanced the flexural properties of the composites. Random dispersion with 10 wt% treated SC yielded the best results among the tested methods, making it the optimal approach for sustainable decoration and architectural materials.